Systematic Review of Health Economic Evaluation Studies Developed in Brazil from 1980 to 2013 - Decimoni, Tassia Cristina; Leandro, Roseli; Rozman, Luciana Martins; Craig, Dawn; Iglesias, Cynthia P.; Novaes, Hillegonda Maria Dutilh; de Soárez, Patrícia Coelho (Frontiers in Public Health, 2018)
Background Brazil has sought to use economic evaluation to support healthcare decision-making processes. While a number of health economic evaluations (HEEs) have been conducted, no study has systematically reviewed the quality of Brazilian HEE. The objective of this systematic review was to provide an overview regarding the state of HEE research and to evaluate the number, characteristics, and quality of reporting of published HEE studies conducted in a Brazilian setting. Methods We systematically searched electronic databases (MEDLINE, EMBASE, Latin American, and Caribbean Literature on Health Sciences Database, Scientific Electronic Library Online, NHS Economic Evaluation Database, health technology assessment Database, Bireme, and Biblioteca Virtual em Saúde Economia da Saúde); citation indexes (SCOPUS, Web of Science), and Sistema de Informação da Rede Brasileira de Avaliação de Tecnologia em Saúde. Partial and full HEEs published between 1980 and 2013 that referred to a Brazilian setting were considered for inclusion. Results In total, 535 studies were included in the review, 36.8% of these were considered to be full HEE. The category of healthcare technologies more frequently assessed were procedures (34.8%) and drugs (28.8%) which main objective was treatment (72.1%). Forty-four percent of the studies reported their funding source and 36% reported a conflict of interest. Overall, the full HEE quality of reporting was satisfactory. But some items were generally poorly reported and significant improvement is required: (1) methods used to estimate healthcare resource use quantities and unit costs, (2) methods used to estimate utility values, (3) sources of funding, and (4) conflicts of interest. Conclusion A steady number of HEE have been published in Brazil since 1980. To improve their contribution to inform national healthcare policy efforts need to be made to enhance the quality of reporting of HEEs and promote improvements in the way HEEs are designed, implemented (i.e., using sound methods for HEEs) and reported.